PERAN MP3EI BERBASIS â€NOT BUSINESS AS USUALâ€ UNTUK MENINGKATKAN DAYA SAING DAN PENYERAPAN TENAGA KERJA - Sahaya, Hardiansyah Nur; Arto, Ali (Universitas Negeri Semarang, 2012)
Indonesia, as a developing country, is currently facing a tremendous challenge. Global era can be an opportunity, a challenge, as well as a threat. In this globalization era, known as economic liberalization or free trade in services in particular labor. Indonesian workers are expected to be able to compete with workers from other countries. To meet the challenges of globalization workforce, the government has prepared MP3EI (Master Plan for the Acceleration and Expansion of Indonesia's Economic Development) which is not based on common business. MP3EI is a government program that is made by considering the various advantages and potential, as well as the development challenges that Indonesia must face. However, in the implementation of the strategic role of MP3EI, there are still problems in terms of human resources, science and technology. Education focuses mainly on Java, less access to education, use of science and technology training, lack of infrastructure investment training. Therefore, we need a concrete solution in optimizing regional autonomy to address the education gap in each corridor, develop the concept of